2004
DOI: 10.1029/2003gl018766
|View full text |Cite
|
Sign up to set email alerts
|

Tracking a major interplanetary disturbance with SMEI

Abstract: [1] We present the first clear observations of an Earthdirected interplanetary disturbance tracked by the Solar Mass Ejection Imager (SMEI). We find that this event can be related to two halo CMEs seen at the Sun about 2 days earlier, and which merged in transit to 1 AU. The disturbance was seen about 16 hours before it reached Earth, and caused a severe geomagnetic storm at the time which would have been predicted had SMEI been operating as a real-time monitor. It is concluded that SMEI is capable of giving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 5 publications
0
61
0
Order By: Relevance
“…Thus not only the magnitude but also the sign of the acceleration can be in error. These ICME accelerations are crucial for predicting space weather effects and for modeling the drag or acceleration forces [Tappin et al, 2004;Tappin, 2006;Howard et al, 2006].…”
Section: A3 Comparisons Of Positions and Speeds For The Methodsmentioning
confidence: 99%
“…Thus not only the magnitude but also the sign of the acceleration can be in error. These ICME accelerations are crucial for predicting space weather effects and for modeling the drag or acceleration forces [Tappin et al, 2004;Tappin, 2006;Howard et al, 2006].…”
Section: A3 Comparisons Of Positions and Speeds For The Methodsmentioning
confidence: 99%
“…However, the SMEI team also produces significant scientific results directly from the 2-D sky map orbit differences (e.g., Tappin et al, 2004;Reiner et al, 2005;Tappin, 2006;Webb et al, 2006Webb et al, , 2009bTappin and Howard, 2009 approximately the same location and morphology of this CME sequence in the ecliptic plane from both instruments as it moves outward from the Sun (e.g., Webb et al, 2009a). These CMEs were also viewed and measured nearer the solar surface by the Large Angle Spectrographic Coronagraphs (LASCO) (Brueckner et al, 1995) on board the SOlar and Heliospheric Observatory (SOHO) spacecraft (Domingo et al, 1995) nearer the solar surface.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that significant deceleration is required for the 15 April CME-driven shock to reach L1 with a speed of 422 km/s given a required, average velocity of 700 km/s, necessary to satisfy the time of flight to reach L1 at midnight 18 April. This is in contrast to the Tappin et al (2004) case study focusing on a May 2003 CME that was tracked using the Solar Mass Ejection Imager (SMEI); an "all sky" coronagraph. The results of this case study suggested the CME in question propagated from the Sun to 1 AU with an almost constant velocity of ∼900 km/s.…”
Section: Discussionmentioning
confidence: 96%